Suitability of various substrates for cultivation of Pleurotus pulmonarius in Konkan Region of Maharashtra - Borkar, Pramod; Doshi, Anila; Joshi, Makarand; Rite, Shrikant (Mushroom Research, 2016)
Mild tropical humid climate persists in Konkan region throughout the year within a range of 23 - 35 Â C which isÂ  conducive for the cultivation of oyster mushroom. To explore the possibilities for commercial cultivation of oyster mushroom with various locally available agro residues in this region, such as paddy straw, wheat straw, arecanut husk, coconut husk, banana pseudostem, groundnut shells andsugarcane bagasse were selected as substrates. Out of the agro residues selected, maximum biological efficiency of 76.30 % was recorded on paddy straw followed by 74.53 % in wheat straw. The BE increased to 85.40 % when paddy straw supplemented with wheat bran This was followed by the BE of 82.63 % when paddy straw supplemented with rice bran and BE of 82.26 % when wheat straw supplemented with wheat branÂ